Virtual Simulation Tools for Communication Skills Training in Health Care Professionals: Literature Review - Manuel Fernández-Alcántara; Silvia Escribano; Rocío Juliá-Sanchis; Ana Castillo-López; Antonio Pérez-Manzano; M Macur; Sedina Kalender-Smajlović; Sofía García-Sanjuán; María José Cabañero-Martínez (JMIR Medical Education)
Abstract BackgroundQuality clinical care is supported by effective patient-centered communication. Health care professionals can improve their communication skills through simulation-based training, but our knowledge about virtual simulation and its effectiveness and use in training health professionals and students is still growing rapidly. ObjectiveThe objective of this study was to review the current academic literature to identify and evaluate the virtual simulation tools used to train communication skills in health care students and professionals. MethodsThis review was carried out in June 2023 by collecting data from the MEDLINE/PubMed and Web of Science electronic databases. Once applicable studies were identified, we recorded data related to type of technology used, learning objectives, degree of learning autonomy, outcomes, and other details. ResultsWe found 35 articles that had developed and/or applied a virtual environment for training communication skills aimed at patients, in which 24 different learning tools were identified. Most had been developed to independently train communication skills in English, either generally or in the specific context of medical history (anamnesis) interviews. Many of these tools used a virtual patient that looked like a person and had the ability to vocally respond. Almost half of the tools analyzed allowed the person being trained to respond orally using natural language. Of note, not all these studies described the technology they had used in detail. ConclusionsMany different learning tools with very heterogeneous characteristics are being used for the purposes of communication skills training. Continued research will still be required to develop virtual tools that include the most advanced features to achieve high-fidelity simulation training.